Challenges in Implementing International Norms and Laws on Women’s Rights in Pakistan - Tooba Razzaq; Waheed Ahmad Khan; Muhammad Ilyas Ansari (ASIAN Journal of International Peace & Security (AJIPS), 2025)
Even though Pakistan has ratified various international treaties and expressed commitment to international norms regarding women’s rights, translating these obligations into effective implementation remains a significant challenge. The continued societal marginalization of women results in their limited participation in social, political and economic spheres. This study explores the key barriers to women’s empowerment, including limited access to education, employment, economic resources and legal protection from violence. Based on an analysis of national and international documents as well as interviews with experts and policymakers from Lahore and Islamabad, it was found that the major obstacles, such as patriarchal norms, biased religious interpretations, limited political representation, financial dependency and outdated legal frameworks are contributing to the lack of implementation of international laws and obligations in Pakistan. It is recommended that efforts such as legal reforms and public awareness campaigns are urgently needed to address legal barriers and social resistance to ensure the effective application of international women’s rights laws. Furthermore, it is essential to strengthen and support civil society actors, including NGOs, to implement international norms and laws at societal level.